Pseudo 4D projective coordinate-based multi-base scalar multiplication - Ming XU; Liang SHI (Tongxin xuebao)
In order to address the problem of elliptic curve cryptosystem (ECC) for the expensive cost in scalar multiplication and the vulnerability to the power analysis attacks,a pseudo 4D projective coordinate-based multi-base scalar multiplication was proposed to optimize group operation layer and scalar multiplication operation layer,which aimed at increasing the performance of ECC and resisting common power analysis attacks.Experimental results show that compared with the state-of-the-art algorithms,the proposed algorithm decreases 5.71% of point doubling cost,3.17% of point tripling cost,and 8.74% of point quintupling cost under discrete group operations.When the key length is 160 bit,the proposed algorithm decreases 36.32% of point tripling cost,17.42% of point quintupling cost,and 8.70% of the system cost under continuous group operations.The analyzing of power consumption wave shows that the proposed algorithm can resist SPA and DPA attack.